2014
DOI: 10.4103/0971-4065.127909
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous injection of acrylic glue into renal allograft pseudoaneurysm for control of intractable post-biopsy hematuria

Abstract: We report a 44-year-old male, renal allograft recipient of 1-year duration who had two episodes of steroid responsive acute rejection. He presented with graft dysfunction for which a graft biopsy was performed and was suggestive of mixed rejection. At 2 weeks post-biopsy, patient developed severe pain over the graft site with anuria and graft hydronephrosis (HDN). The HDN and anuria intermittently settled with the passage of blood clots per-urethra. Contrast enhanced computerized tomography was suggestive of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Just one patient required endovascular embolization due to recurrent severe hematuria after 24 hours. Lal et al reported percutaneous injection of acrylic glue and Lipiodol mixture into renal allograft PA in a case of intractable hematuria after biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Just one patient required endovascular embolization due to recurrent severe hematuria after 24 hours. Lal et al reported percutaneous injection of acrylic glue and Lipiodol mixture into renal allograft PA in a case of intractable hematuria after biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided percutaneous injection of embolic agents into the pseudoaneurysm is done in patients who are hemodynamically stable and with unfavorable vascular anatomy or contrast allergy. [6][7][8] Studies have shown success rates of > 90% with angioembolization. 9 However, sufficient large study data are not available on the success rates of percutaneous embolization.…”
Section: Introductionmentioning
confidence: 99%